Effects of Mouth Rinses on Color Stability of Resin Composites - Celik, Cigdem; Yuzugullu, Bulem; Erkut, Selim; Yamanel, Kıvanc (European Journal of Dentistry, 2008)
Objectives: The aim of this study was to evaluate the effects of 3 commercially available mouth rinses on the color stability of 4 different resin-based composite restorative materials.Methods: Forty disc-shaped specimens (10x2 mm) were prepared from each of the following materials: A nanofill composite Filtek Supreme XT (3M/Espe, St. Paul, MN, USA); a packable lowshrinkage composite, AeliteLS Packable (BISCO, Inc, Shaumburg, IL, USA); nanoceramic compositeresin Ceram-X (Dentsply, Konstanz, Germany); a microhybrid composite, and Aelite All-Purpose Body (BISCO). The specimens were then incubated in distilled water at 37°C for 24 hours. The baseline color values (L*, a*, b*) of each specimen were measured with a colorimeter according to the CIELAB color scale. After baseline color measurements, 10 randomly selected specimens from each group were immersed in 1 of the 3 mouth rinses and distilled water as control. The specimens were stored in 20 mL of each mouth rinse (Oral B Alcohol-free, Listerine Tooth Defense Anti-cavity Fluoride Rinse and Klorhex) for 12 hours. After immersion, the color values of all specimens were remeasured, and the color change value ΔE*ab was calculated. Data were analyzed using a 2-way analysis of variance at a significance level of .05.Results: All specimens displayed color changes after immersion, and there was a statistically significant difference among restorative materials and mouth rinses (P<.05); however, the change was not visually perceptible (ΔE*ab<3.3). The interaction between the effect of mouth rinses and type of restorative materials was not statistically significant (P>.05).Conclusions: It may be concluded that although visually nonperceptible, all resin restorative materials tested showed a color difference after immersion in different mouth rinses. (Eur J Dent 2008;2:247-253)
Keywords: Mouth rinse; Resin composites; Color